Trade Facilitation in Ghana: Critical Review of GATT X - Antwi, Kofi (2011)
The focus of this study was to design and conduct a qualitative research into trade facilitation in Ghana reviewing the impact of trade facilitation measures globally and looking into the level of compliance by Ghana the General Agreements on Trade and Tariff Article X (GATT X) by the World Trade Organisation (WTO). Local stakeholders including GRA/ Customs (customs), Clearing and Forwarding agents (Clearing agents) and importers or exporters (traders) views on the level of compliance was discovered including identifying the key areas in GATT X to be improved. The information gathered from stakeholders was compared with GATT X. The goal was to understand how stakeholders perceive the level that Ghana had reached in terms of GATT X implementation.